The Importance of Fathers Roles in Early Childhood Care - Ita Ilmawaddah; Sofi Affia (Inovan Publisher, 2025)
The importance of father involvement in child care has become a topic that is often researched, both internationally and in Indonesia. However, in Indonesia, the role of fathers in child care is still not optimal. active that involves physical, affective and cognitive. This article was written using the literature study method. This research shows that the presence of fathers in children's lives has a significant role, especially in children's social development. Fathers, as part of the family, are expected not only to be breadwinners but also to contribute actively in parenting to create optimal child development. Father's involvement in raising children has a significant impact on three main domains, namely cognitive, affective and behavioral. supervising, being involved in the child's development process, being a provider of needs, showing affection, protecting, providing emotional support, carrying out responsibilities, nurturing, caring for children, sharing pleasant moments, being present when needed, making plans, and participating in various activities together.